Leech Extract Enhances the Pro-Angiogenic Effects of Endothelial Cell-Derived Exosomes in a Mouse Model of Ischemic Stroke - Yushuang Cao; Jin Sun; Lichen Guo; Meng Wang; Linlin Su; Tong Zhang; Shaoxia Wang; Lijuan Chai; Qing Yuan; Limin Hu (Current Issues in Molecular Biology)
Background: Intercellular communication, facilitated by exosomes (Exos) derived from endothelial cells (ECs), significantly influences the regulation of angiogenesis. Leech extract significantly reduces ischemia–reperfusion injury, promotes angiogenesis, and improves neurological function in mice with stroke. However, further investigation is required to determine whether leech promotes angiogenesis through EC-Exo. Objective: This study aims to further explore whether leech regulates Exos to promote the establishment of collateral circulation in mice with ischemic stroke (IS) and the specific mechanisms involved. Methods: Here, we utilized an in vitro co-culture system comprising ECs and pericytes to investigate the impact of Leech-EC-Exo on enhancing the proliferation and migration of mouse brain microvascular pericytes (MBVPs). We further established an in vivo mouse model of middle cerebral artery occlusion/reperfusion (MCAO/R) to investigate the effects and underlying mechanisms of leech on collateral circulation establishment. Results: The findings demonstrated that leech significantly enhanced the in vitro cell migration number and migration number of pericytes. Therefore, it can also enhance the effect of EC-Exo on improving the infarct area and gait of mice, as well as modulating the HIFα-VEGF-DLL4-Notch1 signaling pathway to promote cerebral angiogenesis and facilitating the stable maturation of neovascularization in vivo. Conclusions: These results suggest that leech has the potential to enhance collateral circulation establishment, and its mechanism may involve the modulation of miRNA content in Exos and the promotion of signaling pathways associated with angiogenesis and vascular maturation.